Smallholders’ perspectives on sustainable agriculture intensification in Northern Ghana - Boateng, E. N. K.; Atampugre, Gerald; Solis, P.; Mariwah, S.; Mensah, I.; Furst, C.; Nyarko, B. K. (Elsevier, 2025)
In the quest to improve food security for a growing population with minimal environmental impact, assessing smallholders’ perceptions and practices of sustainable agriculture intensification (SAI) is a prerequisite for achieving Sustainable Development Goal (SDG) 2. However, little empirical evidence exists on smallholders’ perspectives on SAI, especially in the context of Sub-Saharan Africa, where a majority of smallholders are relatively poor and live under harsh climatic conditions. This research assessed smallholders’ perspectives on the practice of SAI in the Guinea Savanna Agro-Ecological Zone. Data was collected from 698 smallholders in the Bongo and Bolgatanga Municipalities based on a cross-sectional design. It was found that smallholders practised moderate SAI and the positive predictors of SAI adoption were age, monthly income, religion, slope, vegetation and water access, while the negative predictors were farm size, land surface temperature, distance to a dam and land tenure. Based on the assessment of perceived external drivers of adoption, it was found that poor groundwater quality, lapses in government policies on agriculture and lack of engagement in group farming hindered the practice of SAI. It is recommended that non-governmental organizations and government agencies for food and agriculture should enhance efforts aimed at reducing barriers and increasing smallholders’ awareness of how SAI supports their livelihood and contributes to achieving SDG 2.